2015
DOI: 10.1080/01904167.2015.1109117
|View full text |Cite
|
Sign up to set email alerts
|

Non-labile phosphorus acquisition byBrachiaria

Abstract: Brachiaria are tolerant to low phosphorus (P) soils and may enhance P soil availability. The identification of mechanisms driving this effect is important. Our objective was to determine responses of palisade grass and ruzigrass to mineral oxide-bound P. Palisade grass (Brachiaria brizantha) and ruzigrass (Brachiaria ruziziensis) were grown in nutrient solution (NS), where P was supplied as goethite and amorphous aluminum-oxide (Al-oxide). Only half of each pot received P. Dry matter yields of Brachiaria speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…Brachiaria ruziziensis ) is a plant that can grow in various soils, from sandy to clayey, and it develops best in well‐drained soils with good fertility. The biomass production of these plants results in high levels of P and K present in soil . U. ruziziensis has faster decomposition and lower half‐life values than other plants and this in turn leads to nutrient recycling and higher maize yields …”
Section: Introductionmentioning
confidence: 99%
“…Brachiaria ruziziensis ) is a plant that can grow in various soils, from sandy to clayey, and it develops best in well‐drained soils with good fertility. The biomass production of these plants results in high levels of P and K present in soil . U. ruziziensis has faster decomposition and lower half‐life values than other plants and this in turn leads to nutrient recycling and higher maize yields …”
Section: Introductionmentioning
confidence: 99%
“…Brachiaria ruziziensis ), native to the Ruzi Valley in Zaire (Congo) and Burundi, is commonly known as ruzigrass or Congo grass . This species is widely distributed in tropical countries and grows in various types of soils, but it thrives in well‐drained soils with good fertility . Ruzigrass is cultivated for both animal feed and straw supplies for no‐tillage systems .…”
Section: Introductionmentioning
confidence: 58%
“…It is either intercropped with corn or grown as a single crop in rotation with soybeans because of its highly efficiency in producing biomass, which results in high levels of P and K recovery in soils and nutrient recycling . This species also stands out for its adaptability, aggressiveness, and drought‐resistance along with its vigorous growth and high tolerance to acidic soils . In addition, some studies have shown that this species reduces weed emergence in fields …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus (P) uptake by cash crops has been observed to increase after growing cover crops, such as Lablab purpureus and Lupinus albus, due to release of P by the straw decomposition (Horst et al ., ) or due to an increase in soil P bioavailable pools (Calegari et al ., ). Recently, it has been shown that ruzi grass ( Urochloa ruziziensis ) and palisade grass ( Urochloa brizantha ) can mobilize and take up soil recalcitrant P bound to iron (Fe) and aluminium (Al) (Merlin et al ., ). Under no‐till, ruzi grass grown in the soya bean ( Glycine max ) off‐season enhances P cycling decreasing residual–P concentration in deeper soil layers (Almeida & Rosolem, ).…”
Section: Introductionmentioning
confidence: 99%